Histopathological changes induced by saprolegina parasitica in rainbow trout - Doeruecue, Mustafa; Altinterim, Basar (Indian Veterinary Journal, 2008)
Saprolegnia causes death of fish and eggs in the fishes culture industry. Furthermore fish are sensitive to stress factors and environmental conditions which may increase susceptibility to fungus infections. In a previous study (Singhal, et al. 1987), macroscopic and microscopic pathological findings were observed by inoculation of Saprolegnia. After intraperitoneal injection of Saprolegnia, inactivity, altered habitat selection and asphyxia were recorded in fish (Pickering and Wiloughby, 1982). In addition, a reduction in feeding, decrease in vitality and increased mortality were also recorded. The aim of this study was to evaluate the histopathologic changes in the rainbow trout (Oncorhynchis mykiss) experimentally inoculated with Saprolegnia parasitica.